Two new species of Cloeodes Traver (Ephemeroptera: Baetidae) from Espírito Santo, Southeastern Brazil - Massariol, Fabiana Criste; Salles, Frederico Falcão (Zootaxa, 2011)
In the present work, two new species of Cloeodes Traver are described based on nymphs and adults collected in the State of Espírito Santo, Southeastern Brazil. The main characteristics that distinguish the new species from its congeners are, in C. itajara sp. nov.: a) labrum with dorsal arc of setae composed of 12 setae, b) segment III of labial palp with robust and pectinate setae on inner margin, c) fore femur with apex projected, with 5−6 blunt setae, d) male imago with abdominal terga V−VII with a anterolateral triangular black mark; in C. aymore sp. nov.: a) labrum with dorsal arc of setae composed of 1 + 0 + 3 setae, b) fore femur with apex projected, with 2 blunt setae, c) male imago with abdominal terga IV with kidney-like median brown mark.